A Forester in the Himalayas - Hamilton, A. P. F. (Indian Forester, 1975)
In this article, the author, a British Forest Officer who retired as Inspector General of Forests in the year presents a memoir of the early days of his service career in the western Himalayas over half a century ago. He recalls with nostalgia his first impressions of what he regards as the greatest mountain range in the world-"The Castle of the Gods"- of which he had heard so much and which he had always longed to see for himself. The article renders graphic and interesting account of the forest working and management in this mountainous region as it was practised in those early years intervening the two Word Wars. The author discusses some of the problems created by the switch-over from the Selection system to the Shelterwood Compartment system and describes the logging and extraction techniques in vogue at that time. He also makes some interesting personal observations on the occurrence of plant and animal species at the higher elevations - a habit so typical of the early British pioneers of Indian forestry.